Kantian Universalism in Context - van Rijsbergen, Leon (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Proponents of Kantian ethics have paid relatively little attention to the question of whether – and if so, to what extent – Kantian ethics is sufficiently context-sensitive to leave room for morally permissible, different cultural ways of life. An exception to this is Katrin Flikschuh, who proposes an interpretation of Kant's ethics which she refers to as Kantian contextualism. Contrary to standard ‘universalist’ interpretations, Kantian contextualism maintains that the Categorical Imperative can give rise to ‘contextually different substantive principles’, and hence to different moralities for differently situated persons. Flikschuh takes Kantian contextualism, unlike Kantian universalism as it is standardly conceived, to be sufficiently sensitive to different ways of cultural life. In this paper, I provide several arguments for why Flikschuh’s Kantian contextualism should be rejected. Moreover, I will argue that Kantian universalism leaves ample room for cultural pluralism without having to forfeit the idea that the Categorical Imperative puts categorical, universal constraints on action.